The Influence Of Therapy Do'a In Islam To The Cooperative Clients Skizofrenia Cooperative Water Pathway In Public Health Center Karanganyar, Gandusari Trenggalek, East Java - Sunaryo, Sunaryo (Journal Of Nursing Practice, 2018)
Background: Coping mechanism is a process whereby individuals try to handle and master stressful situations that suppress the consequences of the problems it faces, it is very necessary in patients with psychiatric. Purpose : The purpose of this study was to analyze the effect of pre- and post-intervention therapy on cooperative mechanisms of cooperative schizophrenia Methods : The research design used in this research is experimental pre with one group pretest and posttest approach where the mechanism of client cloning before and after Schizophrenia is given intervention in the form of prayer therapy. The analysis used is descriptive where the data is taken directly on each respondent, the score obtained from each respondent will be adjusted with the standard assessment, while testing the hypothesis using t test Dependent analysis. Result : Based on the result of statistical test, the mechanism of cooperative schizophrenia client cooperate in outpatient care in health center of Puskesmas Karanganyar Gandusari District Trenggalek mean difference of therapy of prayer in Islam before therapy and after therapy is 0,400 with standard deviation 0,503. Beside that got value p value = 0,002. Conclusion :The results of this study indicate there is a significant difference between before prayer therapy and after therapy do'a to coping mechanism of client of schizophrenia